Dietary habits and physical activity patterns among medical students in Northern Kerala: a cross-sectional study - Kaithery, Nivya Noonhiyil; Prakash, Pragish; Gangadharan, Navya; Shabeer, Ash Had Mohammed (International Journal Of Community Medicine And Public Health, 2025)
Background: The prevalence of non-communicable diseases (NCDs) in India is on the rise, significantly influenced by poor dietary habits and physical inactivity. Medical students, though academically aware of healthy lifestyles, may not necessarily adhere to them in practice. Objectives were to assess dietary habits among MBBS students of a medical college in Northern Kerala and to evaluate physical activity patterns among the same group. Methods: A descriptive cross-sectional study was conducted among 113 second-year MBBS students at KMCT Medical College, Kozhikode, Kerala, during August-October 2024. A structured, pre-tested questionnaire with 40 items in English was used. It assessed socio demographic data, dietary habits, and physical activity levels. Data were analyzed using SPSS and results presented as percentages and frequencies. Results: The mean age of participants was 21.76±0.92 years; 71.7% were females. While 92% were aware of lifestyle diseases and 98.2% knew the impact of unhealthy foods, 66.4% admitted following an unhealthy diet, and 72.6% expressed a need to improve it. About 52.2% never skipped breakfast, while 87.6% never skipped dinner. Junk food intake was common (98.2%), and only 14.2% consumed fruits daily. Regarding physical activity, 64.6% reported being active, mostly via walking or cycling (63.7%). However, 48% had sedentary time >10 hours/day and 22.1% reported no activity. Laziness (46%) was a major barrier. Conclusions: Despite high awareness, students demonstrated poor dietary and physical activity behaviors. Structured interventions are necessary to bridge the gap between knowledge and practice, especially among future healthcare providers.